Cultural Interference in English Speaking Class - Nurmaisyah Nurmaisyah (JELITA, 2020)
The local culture can give people an advantage in understanding and developing intercultural knowledge and skills. It is also useful for achieving a successful life in this challenging global world. In order to understand people it is important to understand their values and culture. Indonesia consists of various ethnicities, which consequently affect people’s culture as a whole nation. This research was done at one of universities in Makassar, State Islamic University of Alauddin. It comprised 15 respondents from various ethnic backgrounds such as: Makassarese, Buginese, Javanese, and others. The interview used was developed on the basis of Hofstede’s work on values. The study showed that respondents showed five cultural dimensions in speaking which indicated high on Power Distance, Collectivism, Masculinity; and low on Uncertainty Avoidance, and Short and Long Term Orientation.